Metaldehyde intoxication in a red fox (Vulpes vulpes). Issue 1 (2nd May 2014) - Sabater, Mikel; Pérez, Marisa; Calvo Carrasco, Daniel
Abstract : Metaldehyde toxicity has been commonly reported in different species, including dogs, cats, horses, livestock and wildlife, but the authors are not aware of previously described cases in red foxes. A juvenile red fox ( Vulpes vulpes ) intoxicated with metaldehyde was presented and successfully treated, allowing it to be released back into the wild. Clinical signs, diagnostic test results, treatment and evolution for this case are described and a review made about metaldehyde intoxication. Red foxes are abundant native species in the UK and metaldehyde is still used as a mollusc control measure. This case report is written to provide more information about metaldehyde intoxication in this species.